HUBUNGAN KINERJA OTAK DAN SPIRITUALITAS MANUSIA DIUKUR DENGAN MENGGUNAKAN INDONESIA SPIRITUAL HEALTH ASSESSMENT PADA PEMUKA AGAMA DI KABUPATEN HALMAHERA TENGAH - Yastab, Rezky A.; Pasiak, Taufiq; Wangko, Sunny (Universitas Sam Ratulangi, 2014)
Abstract: Human brain contains 100 billions of nerve cells which have a complex function as the control center of all human activities. Related to the brain function, neuroscience emerges, focusing on the nervous system especially the neuron cells. The neuroscience has also significant interest in the relation of human to God. Spirituality refers to things that deal with the spirit or soul, and not attributable to physical nature. Its material consists of two variables: spirituality and domination of the brain. Indonesia Spiritual Health Assessment (ISHA) is an assessment based on the concept of theoretical spirituality. ISHA has three components, namely spiritual health item, examination the brain system assessment, and neurofeedback. This study aimed to obtain the relation of brain with human spirituality in the performance of religion leaders in middle Halmahera. This was a descriptive study with a cross sectional design. Samples were 55 religion leaders. The Spearman correlation test showed a value of sig > Î± with a significance of 0,05. The analytical results showed that the correlation between the limbic system and ritual 0.806; between the prefrontal cortex and the meaning of life 0.833; and between the prefrontal cortex and spiritual experience 0.091. Conclusion: There was no correlation between brain performance and spirituality of the religion leaders in middle Halmahera. Keywords: brain, neuroscience, spirituality, ISHA Â Â Abstrak: Otak manusia tersusun oleh sekitar 100 miliar sel neuron dengan fungsi kompleks sebagai pusat pengendali seluruh aktivitas manusia. Terkait dengan keberadaan otak, berkembang disiplin ilmu neurosains yang khusus mempelajari sistem saraf, terutama neuron, serta hubungan manusia dan Tuhan. Spiritualitas yaitu segala sesuatu yang berhubungan dengan roh atau jiwa, dan tidak berkaitan dengan alam fisik/jasmaniah. Materi spiritualitas terdiri dari 2 variabel yaitu spiritualitas dan dominasi otak. Indonesia Spiritual Health Assessment (ISHA) adalah asesmen yang dibuat berdasarkan konsep teoritis spiritualitas, yang terdiri dari tiga komponen pemeriksaan yaitu Spiritual Health Item, Brain System Assessment, dan neurofeedback. Penelitian ini bertujuan untuk mengetahui hubungan kinerja otak dan spiritualitas manusia pada pemuka agama di Kabupaten Halteng. Penelitian ini bersifat deskriptif dengan pendekatan cross sectional. Sampel penelitian ialah 55 pemuka agama. Uji korelasi Spearman menunjukkan koefesien nilai sig > Î± dan taraf kemaknaan 0,05. Hasil analisis memperlihatkan korelasi Â antara sistem limbik dan ritual 0,806, antara korteks prefrontal dan makna hidup 0,833, serta antara korteks prefrontal dan pengalaman spiritual 0,091. Simpulan: Tidak terdapat hubungan antara kinerja otak dan spiritualitas pada pemuka agama di Kabupaten Halteng diukur dengan ISHA. Kata kunci: otak, neurosains, spiritualitas, ISHA